The Purge Characteristics and Strategy in a Proton Exchange Membrane Fuel Cell with a Linear Segmentation-Based Anode Recirculation System - Weihao Guo; Xiaoxuan Mu; Weida Shen; Chaoqi Ma; Jie Yu; Fu Wang; Jinliang Yuan (Energies)
This study introduces a novel linear segmentation method to optimize the nitrogen purge strategy for proton exchange membrane fuel cells (PEMFCs) operating in an anode recirculation mode. The method simplifies the design of purge cycles by eliminating the need for complex mathematical modeling and multivariable optimization, making it more suitable for industrial applications while avoiding the need for lengthy orthogonal experiments. By experimentally determining the maximum tolerable nitrogen accumulation time and leveraging the linear relationship between nitrogen accumulation and purge duration, the traditional long-cycle purge process is divided into multiple short cycles, establishing an optimal nitrogen discharge strategy. Experimental results demonstrate that the segmented purge cycles significantly reduce voltage fluctuations and improve voltage uniformity across cells. Notably, using a purge threshold with a 30 s closing time and a 2 s opening time resulted in a 19.8% improvement in voltage uniformity. In addition, a detailed analysis of the hydrogen consumption during the purge cycle reveals that an excessive purge frequency leads to significant hydrogen losses, whereas prolonged purge cycles may allow nitrogen accumulation to adversely affect voltage stability. By balancing these effects, the proposed strategy maintains the operational efficiency within the ideal range of 50–60%.